Has the frequency of invasive higher plants stabilized? Results from a long‐term monitoring program of Danish habitats. Issue 2 (18th March 2019) - Damgaard, Christian; Nygaard, Bettina; Ejrnæs, Rasmus; Bruus, Marianne; Strandberg, Beate; Strandberg, Morten; Timmermann, Allan; Ehlers, Bodil K
Abstract: Questions: The change in the frequencies of invasive higher plant species in different habitat types was investigated using Danish monitoring data from 2004 to 2014. Location: Denmark. Methods: The occurrence data were collected in circles with a radius of 5 m at a number of plots within 923 sites. The sampling intensity was irregular with sampling intervals ranging from one to three years. The hierarchical occurrence data were fitted in a hierarchical model, where the site‐specific occurrence probabilities were modelled by latent variables. Results: The overall frequency of invasive higher plant species increased significantly in this 11‐year period in two of the seventeen habitat types, i.e. on coastal dunes and on dry heathland. The frequency of the dominating invasive species, Rosa rugosa, Pinus contorta, and Prunus serotina, was observed to increase significantly in three, two, and one out of the seventeen habitat types, respectively, whereas the frequency of Pinus mugo was found to decrease significantly in one habitat type. Conclusions: The frequency of invasive higher plant species has not stabilized and is still increasing in some or several Danish habitat types. Furthermore, trend analyses of a selected subset of invasive plant species may serve as an important early warning signal that may be used in the management of ecosystems. Abstract : The overall frequency of invasive higher plant species increased significantly in an 11‐year period in two out of the seventeen Danish habitat types, i.e. on coastal dunes (shown here) and on dry heathland. Consequently, the frequency of invasive higher plant species has not stabilized and is still increasing in some habitat types.